2016
DOI: 10.1111/pedi.12429
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of PTPN22 c.1858CC and FCRL3 -169CC genotypes as a biomarker of preserved residual β-cell function in children with type 1 diabetes

Abstract: Ascertained phenomenon could be explained by an interacting mechanism of the two polymorphisms through estrogen-regulated nuclear factor kappa B signaling in regulatory T (T ) lymphocytes. This hypothesis, if confirmed, may lead to further development of T administration-based therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The general dynamics of residual β-cell function and HbA1c level in the patient group throughout the 24-month followup period was previously described. 11 There were noticed no significant differences in dynamics trends of FCP and HbA1c level depending on the gender. The parallel time trends in FCP and HbA1c level were observed in the subgroups divided according to the DKA development at T1DM onset with significantly lower FCP levels throughout the follow-up and corresponding inversely proportional HbA1c levels in patients with DKA development.…”
Section: General Trends In Residual β-Cell Function and Hba1c Level Dmentioning
confidence: 80%
See 2 more Smart Citations
“…The general dynamics of residual β-cell function and HbA1c level in the patient group throughout the 24-month followup period was previously described. 11 There were noticed no significant differences in dynamics trends of FCP and HbA1c level depending on the gender. The parallel time trends in FCP and HbA1c level were observed in the subgroups divided according to the DKA development at T1DM onset with significantly lower FCP levels throughout the follow-up and corresponding inversely proportional HbA1c levels in patients with DKA development.…”
Section: General Trends In Residual β-Cell Function and Hba1c Level Dmentioning
confidence: 80%
“…Inclusion and exclusion criteria with detailed synopsis of the patient group were given in our previous study. 11 After baseline hospitalisation at the time of T1DM diagnosis patients were followed-up by further 24 months.…”
Section: Study Group and Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahallawi and Suliman [599], Vanderheiden et al [600], Moustaqil et al [601], Li et al [602], McGee et al [603], Spoerl et al [604], Seale et al [605], Jeong et al [606], Pérez-García et al [607], Murch, [608], Virant-Klun and Strle [609], Bonyek-Silva et al [610], Neri et al [611], Delaveris et al [612], Brandão et al [613], Solerte et al [614], Duncan-Lowey et al [615], Zheng et al [616], Jamaly et al [617], Nassir et al [618], Liang et al [619], Vietzen et al [620], Kisserli et al [621], Ercan et al [622], Oliviero Ercan et al [623], Mpekoulis et al [624], Acar et al [625], Maione et al [626], Ehsani, [627] and Callahan et al [628] showed that TLR8, CCR2, NLRP12, PECAM1, ITK (IL2 inducible T cell kinase), CCR4, GPX1, TLR1, CCL5, CD33, BSG (basigin (Ok blood group)), ALOX5, SELPLG (selectin P ligand), SIGLEC9, TLR4, DPP4, NLRC4, TLR2, CAMK4, FCGR3B, CXCL5, KLRC2, CR1, F13A1, CXCL10, DDC (dopa decarboxylase), CRP (C-reactive protein), IL17A, HAMP (hepcidin antimicrobial peptide) and CXCL9 were associated with progression of COVID 19. Ahmad et al [629], Sireesh et al [630], Di Prospero et al [631], Anjosa et al [632], Aparicio et al [633], Rau et al [634], Kim et al [635], Thude et al [636], Njerve et al [452], Eldor et al [637], Ferjeni et al [638], Zurawek et al [639], Yang et al [106], Li et al [285], Liu et al [640], Pacifici et al [641], Huang et al [642], Zhang et al [643], Pawłowicz et al [644], Ramos-Lopez et al [645], Bonyek-Silva et al [610], Abu El-Ella et al [646], Mi et al [647], Swafford et al [648], Doody et al [649], Barchetta et al [650], Xu et al [651], Li et al [652], Demirci et al [653], Hasani Ranjbar et al [654], Puchałowicz and Rać [655], Fejes et al [656], Kawabata et al […”
Section: Discussionmentioning
confidence: 99%
“…Previous reports revealed that there was a sharp decrease in the frequency of the variant 620W allele from Northern to Southern Europe, i.e. from around 12.5% in the English and Finnish populations, to approximately 6% in the Italian and Spanish populations [ 18 , 25 26 ]. The variant 1858T allele was reported to be absent from Asian populations [ 27 28 ].…”
Section: Introductionmentioning
confidence: 99%